Byron and the Politics of Freedom and Terror - Pal-Lapinski, Piya. author. aut Link
XIII, 237 p.
Keywords: This interdisciplinary collection explores the divergence or convergence of freedom and terror in a range of Byron's works. Challenging the binary opposition of historicism and critical theory, it combines topical debates in a manner that is sensitive both to the circumstances of their emergence and to their relevance for the twenty-first century.